The Effectiveness Of Buzz Groups Method To Teach Reading Comprehension Viewed From Students’ Learning Motivation (An Experimental Study At The Mechanical Engineering Department Students Of Balikpapan State Polytechnic) - Elisabeth Milaningrum; Subur Mulyanto (JST (Jurnal Sains Terapan), 2016)
Abstract This research is aimed at finding out whether: (1) Buzz Groups Method is more effective than Direct Instruction Method to teach reading comprehension at mechanical engineering department students of Balikpapan State Polytechnic; (2) the students who have high motivation have better reading comprehension than those who have low motivation at mechanical engineering department of Balikpapan State Polytechnic; and (3) there is an interaction between teaching methods and students’ learning motivation for teaching reading comprehension at mechanical engineering department of Balikpapan State Polytechnic. The method which was applied in this research was experimental study. It was conducted at Balikpapan State Polytechnic. The population of the research is the mechanical engineering department student in Balikpapan State Polytechnic. The samples were two classes. Each class was divided into two groups (the students who have high and low motivation). The data analysis shows the following findings: (1) Buzz Groups Method is more effective than Direct Instruction Method to teach reading comprehension to the mechanical engineering department students; (2) The students having high motivation have better reading comprehension than those having low–one; and (3) There is an interaction between the teaching methods and students’ learning motivation for teaching reading comprehension. It means that the effectiveness of the teaching methods depends on the degree of the students’ learning motivation to the mechanical engineering department students. Keyword: Teaching methods, Reading Comprehension, Students’ Learning Motivation